Effects of Combination of Antidiabetic Agent and Statin on Alloxan-induced Diabetes with Cardiovascular Diseases in Rats - Islam, M. S.; Alam, A. H. M. K.; Rahman, M. A. A.; Ali, Y.; Mamun, Al; Rahman, M.; Hossain, A. K. M. M.; Rashid, M. (Journal of Scientific Research, 2012)
The present study was designed to investigate the effects of combination drugs (metformin and atorvastatin) on long-term alloxan-induced diabetes with CVD in rats. In short-term alloxan-induced diabetic rats, metformin reduced significant amount of glucose in blood, but it had no significant effect on lipid profile. Atorvastatin significantly reduced TC, TG and LDL-C, whereas it increased significant amount of HDL-C. However, pathological changes of heart were not observed after short-term induction of alloxan in rats. In long-term induction of diabetes by alloxan, LV hypertrophy was observed and cardimyocyte size in rats was increased. Atorvastatin alone and in combination with metformin significantly reduced the LV hypertrophy, cardiomyocyte size, TC, TG and LDL-C level. They increased significant amount of HDL-C level and showed significant DPPH free radical scavenging activity. Present findings may suggest that treatment with combination therapy is more effective than mono-therapy for preventing diabetes with CVD in rats. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i3.9974 J. Sci. Res. 4 (3), 709-720 (2012)